International standardization and trade regulation : exploring linkages between international standardization organizations and international trade agreements - Klotz, Sebastian (World Trade Institute advanced studies ;, 2024)
"As tariffs have fallen dramatically over the past decades, behind-the-border measures-such as technical barriers to trade (TBT) and sanitary and phytosanitary (SPS) measures-have become increasingly important for international trade policy. To facilitate trade, governments sign trade agreements in which they agree to base such measures on international standards. But who actually develops these standards? This book takes a close look at the International Organization for Standardization and the Codex Alimentarius - two prominent standard-setting organizations in the area of TBT and SPS - to investigate how international standardization influences the design of international trade agreements, and vice versa"--